Towards Quality Graduate Mathematics Teacher Education: A PNU CGSTER Tracer Study - Belecina, Rene R; Ocampo, Jr., Jose M (ASPENSI in Bandung, Indonesia, 2017)
ABSTRACT: Tracer study is one way of evaluating curricular programs, especially in higher education institutions. For the purpose of quality assurance of course programs, higher education institutions can contribute meaningfully by applying the principles of tracer study to create sustainable learning empowerment environment for the continuous professional development of past students. Hence, tracer study can be used for the enhancement of quality course programs offered in higher education institutions to be able to meet the demands of changing educational, socio-economic, industrial and technological demands of the new century. This tracer study evaluated the graduate Mathematics education program in CGSTER PNU (College of Graduate Studies and Teacher Education Research, Philippine Normal University) in Manila, Philippines. The profile of the graduates of the program was described in terms of biographical characteristics, employment attributes, transition, and professional achievements. Likewise, a retrospective evaluation of the program was also done, which includes the satisfaction of the graduates with services, learning environment, and facilities of the university. The extent to which the graduate Mathematics education program contributed to the general and specific competencies of the graduates was also determined. Findings reveal that the graduates are satisfied with the services and facilities of the university. They find the trainings provided by the Mathematics education program adequate and relevant to the skills and competencies they need in their work. Â KEY WORD: Quality Graduate; Mathematics Education Program; Tracer Study; Biographical Characteristics; Satisfaction of the Graduates.Â Â RESUME: âMenuju Kualitas Pendidikan Guru Matematika Pascasarjana: Studi Pelacakan Alumni CGSTER PNUâ. Studi pelacakan alumni merupakan salah satu cara untuk mengevaluasi program kurikuler, terutama di perguruan tinggi. Untuk tujuan penjaminan mutu program studi, perguruan tinggi dapat berkontribusi secara bermakna dengan menerapkan prinsip studi pelacakan alumni untuk menciptakan lingkungan yang memberdayakan pembelajaran berkelanjutan bagi pengembangan profesional dengan masa lalu mahasiswa. Oleh karena itu, studi pelacakan alumni dapat digunakan untuk peningkatan program kursus berkualitas yang ditawarkan di perguruan tinggi agar dapat memenuhi tuntutan perubahan dalam bidang pendidikan, sosio-ekonomi, industri dan teknologi pada abad yang baru. Studi pelacakan alumni ini mengevaluasi program pendidikan Matematika pascasarjana di CGSTER PNU (Sekolah Pascasarjana Penelitian dan Kajian Pendidikan Guru, Universitas Pendidikan Filipina) di Manila, Filipina. Profil lulusan program ini dijelaskan dalam hal karakteristik biografi, atribut ketenagakerjaan, transisi, dan prestasi profesional. Demikian juga, evaluasi retrospektif terhadap program juga dilakukan, yang meliputi kepuasan lulusan dengan layanan, lingkungan belajar, dan fasilitas universitas. Sejauh mana program pendidikan Matematika pascasarjana memberikan kontribusi terhadap kompetensi umum dan spesifik lulusan juga ditentukan. Temuan mengungkapkan bahwa para lulusan merasa puas dengan pelayanan dan fasilitas universitas. Mereka menemukan bahwa pelatihan yang diberikan oleh program pendidikan Matematika memadai dan relevan dengan keterampilan dan kompetensi yang mereka butuhkan dalam pekerjaan mereka.KATA KUNCI: Lulusan Berkualitas; Program Pendidikan Matematika; Studi Pelacakan Alumni; Karakteristik Biografi; Kepuasan Lulusan.Â Â Â About the Authors: Rene R. Belecina, Ph.D. is a Full Professor at the CGSTER PNU (College of Graduate Studies and Teacher Education Research, Philippine Normal University) in Manila, Philippines. Jose M. Ocampo, Jr., Ph.D. is a Full Professor at the Faculty of Education Sciences PNU in Manila, the Philippines. For academic interests, the authors can can be contacted via their e-mails at:Â rrbelecina@yahoo.com and juno_6970@yahoo.comHow to cite this article? Belecina, Rene R. & Jose M. Ocampo, Jr. (2017). âTowards Quality Graduate Mathematics Teacher Education: A PNU CGSTER Tracer Studyâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.10(1) May, pp.45-56. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of the article: Accepted (June 1, 2016); Revised (December 15, 2016); and Published (May 30, 2017).Â Â